Program Pelatihan Karya Inovatif PKB Guru PAUD Urgensi Karya Inovatif PKB Guru PAUD - Reni Supitno; Indah Annisa Rahmi; Isti Hidayati; Khofifah Apriani; Setiyo Utoyo (STIKes Ibnu Sina Ajibarang, 2025)
The of Innovative Initiatives in the Context of Early Childhood Educator Professional Development. Innovative initiatives, including new contributions, modifications, and developments, play a crucial role in enhancing the quality of education and supporting the holistic development of children. This document also outlines a structured training program for early childhood educators that focuses on creativity, professional skills, and effective teaching methods. Through continuous professional development, early childhood educators are expected to produce innovative work that responds to educational challenges and improves the learning environment for children. The primary goal is to create effective, interactive, and meaningful learning experiences while ensuring high-quality education for children. By fostering an environment of innovation, educators can better meet the diverse needs of their students, ultimately contributing to their overall growth and learning success.